Letter - Chepstow Joint Strike Committee, 7 May 1926 (Chepstow)
1926-05-07 "Letter - Chepstow Joint Strike Committee, 7 May 1926" [g0148001.jpg], 7 May 1926, Chepstow Joint Strike Committee Local Organisation